Myoblast Autologous Grafting in Ischemic Cardiomyopathy (MAGIC) Trial - Cunningham, Muriel (MD Conference Express, 2006)
The Myoblast Autologous Grafting in Ischemic Cardiomyopathy [MAGIC] Trial examined the safety and efficacy of autologous skeletal myoblast cell therapy for improving local or global cardiac contractility in patients with ischemic heart failure. This is the first multi-center, randomized, double blind and placebo controlled trial of skeletal myoblast implantation and one that is designed with the power sufficient to determine whether autologous grafting is a viable solution for ischemic cardiomyopathy.